2010
DOI: 10.1016/j.electacta.2010.01.092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnesium on the electrochemical behavior of lithium anode in LiOH aqueous solution used for lithium–water battery

Abstract: a b s t r a c tThe effect of adding magnesium to lithium on lithium electrochemical behavior in 4 mol L −1 LiOH is studied using electrochemical techniques. The results show that the hydrogen evolution rate is decreased with increasing Mg content. Through theoretical analysis and X-ray (XRD) investigation, MgH 2 and Mg(OH) 2 are created on the surface film of lithium-magnesium alloys after discharge. The porosity of the lithium surface film is decreased by MgH 2 , Mg(OH) 2 combined with LiOH and LiOH·H 2 O and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It is noticed that Al(OH) 3 and MgCO 3 are formed in KOH containing CO 2 , while Li 2 CO 3 is formed only on the electrode surface in LiOH under the same conditions 44 . At the same time, H + ions are released as follows: …”
Section: Resultsmentioning
confidence: 86%
“…It is noticed that Al(OH) 3 and MgCO 3 are formed in KOH containing CO 2 , while Li 2 CO 3 is formed only on the electrode surface in LiOH under the same conditions 44 . At the same time, H + ions are released as follows: …”
Section: Resultsmentioning
confidence: 86%
“…Thus, it could be found that a small amount of Mg(OH) 2 could be formed in the β-Li phase during the hydrogen charging process. Zhang et al [44] reported that the mixture of LiOH/Mg(OH) 2 could effectively promote the corrosion resistance of a Li-Mg electrode. Similarly, it could be speculated that the β-Li phase could also be protected by the LiOH/Mg(OH) 2 film.…”
Section: Discussionmentioning
confidence: 99%
“…2 The corrosion reaction of lithium with water resulting in parasitic corrosion. 3,4 The parasitic corrosion reaction is highly undesirable because it produces no useful electrical energy and consumes active lithium. The reaction is highly exothermic and can detrimentally accelerate local corrosion.…”
Section: Introductionmentioning
confidence: 99%